P4 Don't be a stresshead!. (31st December 2017) - Ferguson, KJ; Holman, R; Winters, D; Finlay, A; Gosling, M; Williams, K; Jakeman, N
Abstract : Background: The GMC in their document 'Supporting students with mental health conditions', recognise that stress is extremely common among medical students and that as educators we have a role in recognising this and providing support. 1 Stress itself is not only distressing for the individual but can negatively impact performance. Previous research has found a correlation between the stress produced during simulation and real life scenarios 2 and is therefore an ideal environment to teach about stress in a safe environment. Aim: To determine whether simulation can be used as a tool to teach undergraduate medical students how to positively manage stress in acute scenarios. Methodology: We recruited 18 medical students to participate. They were split into two cohorts. The first underwent a stressful simulation followed by a debrief using the diamond method. This was then followed by another stressful simulation at a later date. The second cohort had the same simulation-debrief-simulation method but with the addition of an afternoon small group teaching session on managing stress inbetween the simulations. Measurable outcomes include heart rate and self-reporting of stress. We used Fitness technology to measure heart rate throughout the simulation scenarios and a variety of scores to measure self-reporting of stress. There was also a free text box for students to describe how they felt during the simulation. Results: Data collection is now complete. The results from the two groups will be compared and statistically analysed using the paired t-test and content analysis will be performed on the free text box responses. Firstly, we hope to gain data to see if repeating simulation helps to reduce stress and anxiety. Secondly by adding in the additional 'managing stress' session we can see if this also influences stress levels independently of simulation. Conclusions: Conclusions will be drawn from the results. References: . GMC. Supporting medical students with mental health conditions. GMC 2015. . Dias RD, Neto AS. Stress levels during emergency care: A comparison between reality and simulated scenarios. Journal of Critical Care 2016;33:8–13.